Theoretical analysis and experimental investigation on a novel self-moving linear piezoelectric stepping actuator. (1st January 2020) - Wang, Liang; Jin, Jiamei; Zhang, Hongxuan; Wang, Fangyi; Jiang, Zheng
Highlights: A novel self-moving linear piezoelectric stepping actuator is proposed in this study. Theoretical analysis is conducted to design the elastic cell. The kinetic characteristic of the proposed actuator is analyzed to identify its two moving modes: stepping and sliding. A high positioning resolution of 7 nm is achieved when the actuator prototype worked in the sliding mode. Abstract: A novel self-moving linear piezoelectric stepping actuator is proposed in this study, to address the performance differences between large strokes and high positioning precision in traditional linear piezoelectric actuators. The proposed actuator is comprised of an elastic cell and three driving units, including three piezo stacks. And it is able to achieve bidirectional movement with high resolution and large-strokes by applying defined sequence electric signals. Theoretical analysis is conducted to design the elastic cell, and the kinetic characteristic of the proposed actuator is analyzed to identify its two moving modes: stepping and sliding. A prototype is manufactured, assembled and experimented to investigate mechanical performances of the proposed actuator. Results indicate that the actuator prototype moves in the two modes according to the excitation voltage value of the input signals. A high positioning resolution of 7 nm is achieved when the actuator prototype worked in the sliding mode. Additionally, frequency sensitive measurements show that the maximum mean velocity of 1.5 mm/s for the actuator prototype is obtained when the driving frequency is 300 Hz. Finally, a maximum loading weight of 2000 g is reached as the excitation voltage is 50 V. The developed actuator presents promising applications in high precision positioning stages.